EDUKASI MENGGUNAKAN MEDIA PODCAST TENTANG PENCEGAHAN KANKER SERVIKS PADA REMAJA PUTRI - Karjatin, Atin; Setiawan, Ridwan (Poltekkes Kemenkes Bandung, 2024)
Cervical cancer is widely found in women in developing countries, with a prevalence of cervical cancer of almost 70%, because the level of awareness about cervical cancer and early detection is still low. The cause of 99% of cervical cancer cases is Human Papilloma Virus (HPV) infection, and WHO data between 2019 and 2021 state that the coverage of the first dose of HPV vaccination fell by 25% to 15%. In Indonesia, HPV vaccine coverage in 2019 was very low, with only 1.1% of all adults receiving the vaccine. The WHO recommends that girls aged 9 to 14 years are the main target for 1 or 2 doses of HPV vaccine because at this time it is very possible to get HPV immunization. Preventive efforts are behaviors related to individual health known as health behaviors, by providing education using cervical cancer prevention podcasts to students. This study aimed to determine the changes in students’ knowledge about cervical cancer prevention after receiving podcast media education. The method used descriptive. Education was carried out 2 times in 41 students with podcast media. The results showed that there was an increase in knowledge about cervical cancer prevention by 14.3% after students were given education with podcasts. Providing education using cervical cancer prevention podcasts to students increases student knowledge, so that it can affect the acceptance of the HPV vaccine.